UNIVERSITIES CONTRIBUTE TO IMPLEMENTATION OF NATIONAL TRANSFORMATION AGENDA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 April 2016 – Universities have significant roles to play and contribute to the implementation of the national transformation agenda.